Effects of congested match periods on acceleration and deceleration profiles in professional soccer - Djaoui, Léo; Owen, Adam; Newton, Matt; Theodoros Nikolaidis, Pantelis; Dellal, Alexandre; Chamari, Karim (Biology of Sport, 2022)
The aim of the present study was to analyse the influence of congested periods of matches on the acceleration (Acc) and deceleration (Dec) profiles of elite soccer players. Twenty-three elite male professional soccer players participated in the study across 31 official matches. Assessed periods included: (i) congested periods (three to four days between games), and (ii) non-congested periods (more than four days between games). Physical activity during matches was recorded during games using a 10Hz global positioning system device, coupled with a 100 Hz accelerometer, and was analysed according to the periods. Maximal Acc- (73.2 ± 20.3 vs. 84.918.5 m), high Acc- (244.0 ± 49.5 vs. 267.0 ± 37.8 m), maximal Dec- (139.0 ± 44.8 vs. 152.039.3 m) and the total decelerating- distance (5132 ± 690 vs. 5245 ± 552 m) were lower in congested than in non-congested periods (p 0.05). It was concluded that Acc and Dec match activities were significantly affected during congested periods compared to non-congested highlighting a possible fatigue accumulation being responsible for the observed decrement in physical activity. Monitoring Acc and Dec metrics throughout particular periods of congested fixtures amongst professional soccer teams is advised and may be a way to assess physical and fatigue status.